2013
DOI: 10.1016/j.ijfatigue.2012.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue crack propagation properties of Ti–6Al–4V in vacuum environments

Abstract: Abstract:To determine the effects of vacuum environment on fatigue crack propagations in a Ti-6Al-4V alloy, K-decreasing tests were conducted in air and vacuum. The fatigue crack propagation rate became slower and threshold stress intensity factor range became larger with decreasing vacuum pressure.The tendency cannot be fully explained by the crack closure. Based on fracture surface observations, granular region of a few micrometer size asperities was observed on the fracture surface only in high vacuum and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
54
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 16 publications
0
54
0
Order By: Relevance
“…While in the results by Morrissey et al [25,26], no facet was found for the similar microstructure of Ti-6Al-4V alloy. the case of positive stress ratios, crack initiation sites with facets were observed at fracture surfaces for Ti-6Al-4V alloy [27][28][29]. This suggested that the increase of stress ratio promoted the occurrence of faceted crack initiation.…”
Section: Introductionmentioning
confidence: 91%
“…While in the results by Morrissey et al [25,26], no facet was found for the similar microstructure of Ti-6Al-4V alloy. the case of positive stress ratios, crack initiation sites with facets were observed at fracture surfaces for Ti-6Al-4V alloy [27][28][29]. This suggested that the increase of stress ratio promoted the occurrence of faceted crack initiation.…”
Section: Introductionmentioning
confidence: 91%
“…The reason for crack initiation from the surface or from both the surface and the interior at R ¼ À1 is not clear. For the positive stress ratio, the results for a Ti-6Al-4V alloy [23,24] indicated that the fatigue strength exhibited a sharp decrease in the HCF and the VHCF regimes for the crack initiation from the interior with facets. It was also reported that cracks initiated occasionally from the surface with subsurface facets at the initiation region [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkable characteristic of the ODA is that the similar fracture surface morphology can be observed for different material systems, i.e. high strength steels and titanium alloys, and that the morphology is found on the fracture surface tested in high vacuum environment (Oguma and Nakamura, 2013). Recent study by Yoshioka and Nakamura, (2016), using synchrotron radiation CT imaging directly observed the initiation and growth of ODAs in Ti-6Al-4V alloy.…”
Section: Introductionmentioning
confidence: 85%